Decoding the unknowns in long covid. (4th February 2021) - Altmann, Daniel M; Boyton, Rosemary J
Abstract : This article is adapted from a piece published on BMJ Opinion in December 2020. The full article can be read here: https://blogs.bmj.com/bmj/2020/12/09/confronting-the-pathophysiology-of-long-covid/